Standar Kompetensi Kerja sebagai Strategi Efektifitas Operasi Perusahaan - Achmadi Achmadi (JUDICIOUS, 2020)
This study aims to provide awareness to company management in developing competencies for its employees. Coaching employees with relevant competencies can improve management quality standards. Based on the classification, this research is classified as applied research (Applied research) with qualitative data. Researchers provide a strategy for developing company quality by increasing the competence of personnel. The researcher triangulated the data by summarizing various scientific sources and related regulations, then validated it by filtering the opinions of management resource practitioners in the company. As a result, the company has effectiveness in developing the competence of its employees. SOPs that are collaborated with competency elements for each stage of operation guarantee the minimum standard quality of the products and services issued. Companies that do not increase their personnel capacity or quality will easily fall behind other companies. Further research is expected to have quantitative measurements so that they can prove the meaning of competency development in company profitability and efficiency